The accidental empress [large type] : a novel - Pataki, Allison (Thorndike Press large print core, 2015)
Allison Pataki follows her critically acclaimed debut, The Traitor's Wife, with the little-known love story of "Sisi," the Austro-Hungarian Empress and captivating wife of Emperor Franz Joseph. Rich period detail and a cast of complex, bewitching characters offer a captivating glimpse into one of history's most intriguing royal families, shedding new light on the glittering Habsburg Empire and its most mesmerizing, most beloved "Fairy Queen."